A MODERN VIEW ON THE PROBLEM OF NON-DEVELOPING PREGNANCY - Akhmedov, F. K.; Akhmadzhonova, G.M.; Askhanova, G.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background. In obstetric practice, no other problem attracts as much attention as the development of preeclampsia (PE) and eclampsia. According to the World Health Organization, preeclampsia is diagnosed in 28% of pregnant women, making up a significant proportion of all hypertensive disorders during pregnancy. In the global structure of maternal mortality, PE accounts for 12%, and in developing countries this figure reaches 30%. Aim. To analyze the nature of the course of pregnancy in women of Uzbek nationality with preeclampsia of varying severity. Materials and methods. The study included 40 women of reproductive age with preeclampsia of varying severity. The control group consisted of 10 women of the same age without signs of preeclampsia. Results. Data analysis showed that in the main group, the frequency of complications such as gestosis, threatened miscarriage and iron deficiency anemia was statistically significantly higher (2-3 times) compared to the control group. In the second half of pregnancy, the threat of premature birth was observed in 25% of women with moderate preeclampsia and in 50% with a severe form of the disease. When comparing the groups, the proportion of patients with the threat of premature birth in the main group was 3-5 times higher than in the control, while the indicator varied from 25.2% with moderate preeclampsia to 50.8% with severe preeclampsia. Premature detachment of a normally located placenta was recorded in 6 of 63 women with severe preeclampsia, accompanied by high blood pressure and severe anemia. Conclusions. Timely detection and correction of pregnancy complications in preeclampsia can significantly improve the prognosis for the successful completion of pregnancy and childbirth.